Association of vitamin D receptor gene polymorphism with young onset diabetes millitus in a Bangladeshi population - Paul, Debashish (BRAC University, 2012)
This thesis report is submitted in partial fulfillment of the requirement for the degree of Masters of Science in Biotechnology, 2010